Educating the Approaches to Intellectual Property as the Trends of Application of Subjective Good Faith in Russian Law - Vasilyev, Artem S. (2020)
In Russian law, the term "good faith" ("good conscience") refers to different concepts: "honest practice" and "ignorance of the fact when such ignorance generates legal consequences." The article investigate  the educational aspects of distinguishing  objective and subjective good faith. The questions of application of the rules on subjective good faith to the relations arising in connection with the establishment, circulation and protection of civil rights are considered. The analysis of the content of the legal regime of objects of absolute property rights (things, property security, share in the right of common property, corporate rights) allowed us to conclude that the consideration of the rules on subjective good faith is a natural, necessary element of the legal regime of any object of civil turnover, and the real question is only the recognition of such an element of the legal regime by the rule of law and the definition of the features of its application.